Conceptual metaphors of Merarik marriage in Sasak society: A cognitive linguistic study - Lidya Rahmawati; Moh. Rajabul Gufron; Siti Wahyu Puji Anggraini (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2026)
This study examines how the Sasak community constructs the meaning of Merarik (traditional Sasak marriage) through conceptual metaphors from a Cognitive Linguistics perspective. Using a qualitative approach, data were collected through naturalistic observation of everyday conversations in Pringgajurang Utara Village, East Lombok. The dataset consisted of 40 Sasak-language expressions related to Merarik. Data were analyzed by identifying the source and target domains and the conceptual mappings underlying each expression. Credibility was established through methodological triangulation, member checking, and peer debriefing. The analysis identified 20 conceptual metaphors, categorized as ontological, structural, and orientational, with ontological metaphors occurring most frequently. The most productive metaphors were Merarik is a Journey, Merarik is an Honor, and Merarik is a Fence. The findings show that the Sasak community conceptualizes Merarik through concrete physical, social, and cultural experiences, understanding marriage not only as a social institution but also as a process of learning, responsibility, social regulation, and cultural identity. These findings support the view that abstract concepts are understood through more concrete experiences and demonstrate how conceptual metaphors reflect culturally embedded understandings of marriage. This study contributes to culturally grounded Cognitive Linguistics by highlighting the relationship between language, cognition, and local cultural practices in the conceptualization of marriage.